Hyperemesis gravidarum: associations with personal and familial history of nausea : a prospective study - Lindström, Venla (My University, 2022)
BACKROUND: Hyperemesis gravidarum (HG) is a disorder with excessive nausea and vomiting during pregnancy. Family history of nausea and vomiting of pregnancy (NVP) and personal history of nausea in different situations have been associated with a higher risk of HG in our earlier, retrospective study. This study focuses on these themes in a prospective setting. OBJECTIVE: To determine whether a personal history of nausea in different circumstances and NVP in relatives are associated with HG. STUDY DESIGN: Women in the HG group (n=102) were recruited among patients hospitalized due to HG. The control group (n=138) consisted of women with no NVP during pregnancy. Personal history of nausea was inquired in relation to ’motion sickness’, ’seasickness’, ’migraine’, ’other kind of headache’, ’after anesthesia’, ’during the use of contraception’ and ’other kinds of nausea’. Relatives with NVP were divided into first- and second-degree relatives. RESULTS: In univariate analysis, personal history of motion sickness, seasickness, nausea with migraine, nausea with other headache and nausea in other situations were associated with HG. Nausea with other headache did not remain significant after adjusting for parity, pre-pregnancy body mass index, age and marital status. In multivariable analysis with all history of nausea variables, motion sickness and nausea during migraine were associated with HG. Having any affected relative, especially a first-degree relative, was associated with HG. Adjustment for parity, pre-pregnancy body mass index, age and marital status did not change the results. CONCLUSIONS: Motion sickness, nausea in migraine and positive family history increased the odds for HG.
Keywords: hyperemesis gravidarum, nausea, nausea and vomiting of pregnancy, heredity